Single-Pixel Imaging for Partially Occluded Objects - Jingjing Wu; Lifa Hu; Jicheng Wang (IEEE Photonics Journal)
In some complex scene, such as military reconnaissance and other fields, the target object may be partially occluded by some opaque obstacles, which increase the difficulty to obtain the complete object image. In traditional optical imaging system, the lenslet array or the reference beam and special algorithms are usually needed to solve this problem, which increase the complexity of the system. As a computational optical imaging technology, the problem of single-pixel imaging (SPI) for an occluded object has not been researched yet as we know. Here we propose an SPI system to recover the occluded object image. Firstly, the images of object and occlusion from different perspectives are obtained by detecting the light field at different positions. Secondly, the limited conditions of the system parameters are derived by using geometric optics theory to ensure complete imaging. Thirdly, the feasibility of the scheme and the correctness of the limited conditions are verified by experiments. The results in this article can promote the application of SPI technology in many complex practices.